Differences and similarities in the translations of U.S. film titles into Latin American and European Spanish (UNIHumanitas, 2021)
This study made a comparison and differentiation of the titles of American films between European and Latin American Spanish through a checklist which was established as indicators: the translation styles, the different functions, dimensions, author's intention, cultural factor among others, which influenced at the moment of making the translation of the film titles. The purpose of this research was not focused on making a critique of the translations, but to present information comparing both Spanish translations and the translation styles used in order to clarify the differences that exist between the European and Latin American Spanish translations, despite the fact that they share the same language. Finally, taking into account a series of factors, theories and principles, it was possible to differentiate and assimilate that translations do not always seek to convey the author's intention or the plot of the film, and as a consequence of this, confusion is generated because many translations are influenced by the commercial factor, completely displacing the author's intention or the plot, considering that it does not seek a connection between them.
Keywords: Audiovisual translation; styles; differentiation; similarity; factors